Peran Keluarga dalam Pencegahan Perilaku Kriminal pada Anak Kajian Kriminologi - Kyla Dwi Azrania; Hasuri Hasuri (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Criminal behavior in children is a complex phenomenon and requires serious attention from various parties, including families. Criminology as a science that studies the causes and prevention of crime provides an important foundation in understanding the role of the family in preventing criminal behavior in children. This research aims to examine the role of the family in preventing criminal behavior in children from a criminological perspective. This study uses literature analysis methods to identify factors that influence children's criminal behavior and the role of the family in preventing it. The results of the analysis show that the family has a significant role in shaping children's character and behavior. Harmonious family conditions, open communication, and the formation of strong moral values can be protective factors in preventing children from being involved in criminal behavior. However, there are also risk factors in the family environment that can increase the likelihood that children will be involved in criminal behavior, such as domestic conflict, neglect, and domestic violence. Therefore, the role of the family in preventing criminal behavior in children needs to be strengthened through intervention programs that support the formation of a healthy family environment and support positive child development. This research concludes that to reduce crime rates among children, preventive measures must involve the active role of the family as the smallest unit in society. By understanding the factors that influence children's criminal behavior and the role of families in preventing it, effective intervention strategies can be designed to create a safe environment and support the quality growth of children.